Ability to Pay in New Zealand's Tax System - Gunnarsson, A (Victoria University of Wellington Law Review, 1997)
This article begins with a review of tax distribution principles and theory to provide a framework to which the position and interpretation of the ability to pay principle can be related. In the next three sections the author describes how the income tax base, the wealth tax and the income support system correspond with the ability to pay principle. Finally, the author looks upon new equity trends in taxation from a New Zealand perspective.